Review information that adresses the topic of anglophone culture literature and reading comprehension in the efl classes (2022)
Implementing anglophone culture literature in classrooms can be useful for EFL students to enhance their reading strategies and expand their cultural knowledge while they connect their own life experiences with the content provided in the different types of literature materials. This monograph is a qualitative study since it seeks to analyze different results once learners prove their reading comprehension development process through anglophone culture reading exercises. This study is also a bibliometric analysis because of the usage of qualitative methods used to analyze content, references, citations, and authorships of different publications. Based on this, there are no research questions or participants. Regarding Diodato (2012), the technique to be followed in this research, to gather information, is setting up the premises as explained as follows: The regarded topic for this study is to review anglophone culture literature to improve reading skills; this study is taking into consideration two key languages to find information such as English and Spanish; Some academic journal sources such as Íkala, Revista de Lenguaje y Cultura, and Revista Colombiana de Educación will be considered to establish the search of information. Other techniques used to collect information are searching, evaluating, and analyzing the criteria and results. With this monograph, I expect to stimulate research regarding the usage of anglophone culture literature in EFL classrooms to improve students’ reading skills.